6(t-3)+4t=5(2t+5)-13

Simple and best practice solution for 6(t-3)+4t=5(2t+5)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(t-3)+4t=5(2t+5)-13 equation:


Simplifying
6(t + -3) + 4t = 5(2t + 5) + -13

Reorder the terms:
6(-3 + t) + 4t = 5(2t + 5) + -13
(-3 * 6 + t * 6) + 4t = 5(2t + 5) + -13
(-18 + 6t) + 4t = 5(2t + 5) + -13

Combine like terms: 6t + 4t = 10t
-18 + 10t = 5(2t + 5) + -13

Reorder the terms:
-18 + 10t = 5(5 + 2t) + -13
-18 + 10t = (5 * 5 + 2t * 5) + -13
-18 + 10t = (25 + 10t) + -13

Reorder the terms:
-18 + 10t = 25 + -13 + 10t

Combine like terms: 25 + -13 = 12
-18 + 10t = 12 + 10t

Add '-10t' to each side of the equation.
-18 + 10t + -10t = 12 + 10t + -10t

Combine like terms: 10t + -10t = 0
-18 + 0 = 12 + 10t + -10t
-18 = 12 + 10t + -10t

Combine like terms: 10t + -10t = 0
-18 = 12 + 0
-18 = 12

Solving
-18 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| .11x-400-.03x=840 | | 4x+6+3x+4=(-40)+4 | | 3z-836=-77 | | Y+8=2y-4 | | -3x+10=94+4x | | 5y^2-7y=-2 | | 27=3(2x-7) | | -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 | | (2x-4)-(5x+3)= | | 4c-43=7c-193 | | 44=4(x-5) | | -43=2+9x | | 3(y-7)=2(4+y) | | 4m=m+21 | | 20x^2-25+5= | | -2=4r-s | | 4(j-3)=23-3j |

Equations solver categories